Education: The basics - Wood, Kay (London Routledge, 2011)
Everyone knows that education is important, we are confronted daily by discussion of it in the media and by politicians, but how much do we really know about education? Education: The Basics is a lively and engaging introduction to education as an academic subject, taking into account both theory and practice. Covering the schooling system, the nature of knowledge and methods of teaching, this book analyses the viewpoints of both teachers and pupils. Key questions are answered, including: What is education and what is it for? Where does education take place? How do we learn? Who are the students? What is being taught in schools and universities and why? What is the state of education across the world? With further reading throughout, Education: The Basics is essential for all those embarking on undergraduate courses in Education and Education Studies, and for those with an involvement in teaching at all levels.
Keywords: Education; Education--Philosophy